Integrasi Pemetaan Digital dan Partisipatif untuk Analisis Spasial Temporal Perubahan Penggunaan Lahan - Tahir, Tahir (Jurnal Penelitian Pendidikan Geografi, 2026)
Digital technology-based mapping in development planning is often unable to capture the dynamics of land use change at the micro scale. Therefore, the integration of spatio-temporal participatory mapping with digital data through overlay analysis is important to produce more accurate, contextual, and inclusive land use change information. This study aims to 1) classify land use types in Lainea District, South Konawe Regency, and 2) analyze land use changes spatio-temporally from 2016 to 2025, to determine the direction of development based on mapping with the community. This study uses terrestrial survey methods and digital survey collaboration using remote sensing data from Landsat-8 and Landsat-9 images. The results show that in the period 2016 to 2025 there was a significant change of 1,411.28 ha. The largest decrease occurred in mixed dryland agricultural land which shrank by 583.85 ha (41.37%) of the total change, followed by swamp scrubland covering -13.84 ha. In contrast, there was a significant increase in rice fields, reaching 528.89 ha (37.45%), and secondary dryland forest, reaching 103.60 ha. Residential and mining areas also increased, although by relatively small percentages. Overall, this trend indicates a shift in land use from shrubland and mixed agriculture to more intensive uses such as rice fields and secondary forests.